Temporal Depression and the Disappearance of Ships. Issue 1 (2nd January 2016) - Clarke, Robert
Abstract: The following dialogue is between two fictional voices that concerns the phenomenological aspects of two closely related and marginal sub-genres: photographs of ships and photographs taken aboard them by their crews. Whereas the first category is defined by its presentation of the external profile of a vessel in a single view, crew's photographs record their own lived experiences through manifold pictures of the "internal" ship. In light of this, the discussion describes and questions the nature of appearance and temporality arising in both kinds of images, for one of the interlocutors.